Improving Science Process Skills and Concept Understanding through Field Study of Class VII.1 Students - Erni Mariana; Ayang Kinasih (Pendidikan Kimia Unimus, 2021)
This study aims: (1). Improve students' KPS (Science Process Skills) abilities through Field Study learning. (2). Improve students' conceptual understanding skills through field study learning. This study uses (PTK) is Classroom Action Research, which is a research activity carried out in the classroom as an effort to study, critically reflect on a lesson plan on teacher performance, teacher-student interactions, and student-class interactions.The results in this study were an increase in the number of students who reached the target from cycle I to cycle II. The results in cycle II have reached the target set, this shows that the application of school-based learning is able to improve students' conceptual understanding. This percentage of achievement shows that students have experienced increased skills in observing, classifying, predicting, measuring, communicating, and concluding. This achievement shows that students have experienced increased understanding in translating, interpreting, and extrapolating. The percentage increase in the achievement of each indicator, namely, translating 13.1%, interpreting 14.4%, and extrapolating 13%. The conclusions in this study are (1). The percentage of improvement in science process skills by using field studies of class VII.1 students on the subject of Substance was 11.05%. (2). The use of field studies can improve the conceptual understanding of class VII.1 students on the subject of Substance by 13.7%.